Effect of antibiotics extracted from Pseudomonas aerugimosa against plant fungal pathogens - Mayudin, Maisarah (2016)
Fungi are among the most important plant pathogens that cause severe yield loss of crops such as rice, maize, fruits and vegetables. This problem may be effectively controlled using fungicides but somehow it will trigger the emergent of new resistant fungi. Furthermore, the usage of chemical control is not the best solution as the environmental pollution is critically high. However, Pseudomonas aeruginosa is one of the Pseudomonas spp that was shown could be used as a biological control agent against plant pathogenic fungi. This research is conducted to extract crude antibiotics from Pseudomonas aeruginosa UPM P3 and to determine the effect of different concentrations of the extracted crude antibiotics on the mycelial growth of selected plant fungal pathogens. Four types of important fungi culture will be maintained for screening. Bacterial suspension will be prepared using Luria Bertani (LB) broth. By using cell-free supernatant, the antibiotics will be extracted and tested against the selected fungal pathogens using poison food technique with six different concentrations (0, 0.1, 0.2, 0.4, 0.8 and 1.0 mg/ml). This experiment was conducted in a completely randomized design (CRD). The assessment of mycelial growth will be done by measuring the diameter of the mycelium for each concentration used and compare with the control treatment. Antibiotics produced by Pseudomonas aeruginosa UPMP3 can be extracted and are expected to inhibit the growth of plant fungal pathogens in vitro.